2017
DOI: 10.47535/1991ojbe013
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction and Loyalty: A Study of Interrelationships And Effects in Nigerian Domestic Airline Industry

Abstract: The debate concerning the interrelationships and effects between customer satisfaction and loyalty has been tossed back and forth, without a consensus opinion. This study examines the linkages between customer satisfaction and loyalty in Nigerian domestic airline industry. The study adopted correlation research design to elicit information via questionnaire from 600 domestic air passengers drawn through convenience sampling technique. The data obtained from the respondents were analysed with Pearson correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
(42 reference statements)
4
22
0
4
Order By: Relevance
“…Examples include satisfaction (e.g. Parasuraman et al , 1988; Raza et al , 2012; Ganiyu, 2017) and trust (e.g. Grewal et al , 2004; Mosavi and Ghaedi, 2012).…”
Section: Discussion Future Work and Conclusionmentioning
confidence: 99%
“…Examples include satisfaction (e.g. Parasuraman et al , 1988; Raza et al , 2012; Ganiyu, 2017) and trust (e.g. Grewal et al , 2004; Mosavi and Ghaedi, 2012).…”
Section: Discussion Future Work and Conclusionmentioning
confidence: 99%
“…They are "attribute satisfaction" which refers to the cognitive and logical establishment of satisfaction by the customer and the "pleasurable satisfaction" which refers to the consumers' affection or emotional reaction toward a product or service. Ganiyu (2017) concluded that customer satisfaction is of extreme importance in building and enhancing customer loyalty and boosting profitability, but is not always sufficient in all cases.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Review of the literature found a strong relationship between satisfaction and loyalty (Bloemer and de Ruyter, 1998; Bridson et al , 2008; Ganiyu, 2017). Customer loyalty is:[…] the biased (i.e.…”
Section: Influences Of Transaction Specific Characteristics On Satisfaction and Loyaltymentioning
confidence: 99%